MULTI-DIMENSIONAL THREAT PERCEPTION: UNDERSTANDING STATE RESPONSES TO COMMUNAL VIOLENCE IN POST-SUHARTO INDONESIA - Zhaowen, Guo (PEOPLE: International Journal of Social Sciences, 2015)
The resignation of Suharto in 1998 was accompanied with locally concentrated communal violence. This study seeks to understand the variation of state responses to communal violence in post-Suharto Indonesia. I argue that threat perception, divided to threat formation and threat evolution, is explanatory in bridging communal violence and state responses.By vertical comparison, I argue that (1) State responses to the outbreak of communal violence depend on threat formation on collective action at societal level; and (2) State responses to the escalation of communal violence depend on threat evolution on collective action at state level. By horizontal comparison, I argue that threat perception of religious violence is stronger than that of ethnic violence.